Delamination failures of Stellite hardfacing in power plants: a microstructural characterisation study. (June 2014) - Lolla, T.; Siefert, J.; Babu, S. S.; Gandy, D.
<x content-type="archive" xml:space="preserve">Abstract</x> In recent years, several incidents of cracking and failures have been observed in Stellite (Stellite is a registered trademark of the Deloro-Stellite Corporation) hardfacing used in valves of modern high temperature combined cycle gas fired power plants. These hardfacing layers are applied as an overlay onto a steel substrate, such as CrMo steel (i.e. Grade 22, WC9) or creep strength enhanced ferritic steel (i.e. Grade 91, C12A). Cracking has been observed in valve components at the Stellite/steel interface and in the weld dilution zone formed between the steel and clad. Ultimately, disbonding or delamination of the weld hardfacing from the valve body occurs and has resulted in collateral damage to components in the plant (such as to the turbine) or valve failure. In this study, the microstructure formed near the Stellite/steel interface is investigated. Based on thermodynamic modelling, microstructure formed at these regions is hypothesised and a simple methodology is proposed to predict the occurrence of these failures.